The fragility of randomized trial outcomes underlying management of dyspepsia and Helicobacter pylori infections. Issue 1 (March 2020) - Meyer, Chase; Bowers, Aaron; Tritz, Daniel; Fuller, Kaleb; Wayant, Cole; Cook, Courtney; Torgerson, Trevor; Som, Mousumi; Vassar, Matt
ABSTRACT: Aim: The fragility index is calculated by changing one outcome event to a nonevent within a trial until the associated P value exceeds 0.05. In this study, we assessed the robustness, risk of bias (RoB), and power of randomized controlled trials that underlie recommendations set forth by the American College of Gastroenterology (ACG) on managing dyspepsia and Helicobacter pylori infections. Methods: All citations referenced in the guidelines were screened for inclusion criteria. The fragility indexes for eligible trials were then calculated. The likelihood and sources of bias in the included trials were evaluated by the Cochrane 'RoB' Tool 2.0. Results: The median fragility index for the 52 trials was three events. Five studies (9.6%) resulted in a fragility index of 0 when statistical analysis was applied. For the 52 trials, 12 (23.1%) were at a low RoB, 15 (28.8%) had some concerns, and 25 (48.1%) were at a high RoB. High RoB was most commonly due to bias of selection in the reported result (15.5%). Conclusion: A median of three events was needed to nullify statistical significance in 52 trials that underpin guideline recommendations on the management of dyspepsia and H. pylori infections. In addition, concerns for RoB were found for these trials. Abstract : Supplemental Digital Content is available in the text